The Correlation Between Three-Dimensional Ultrasound Measurement of Fetal Adrenal Gland and Maternal Serum Fructosamine Level in Gestational Diabetes Mellitus: Prospective Cohort Study - Junhasavasdikul S; Panburana P; Bumrungphuet S; Dulyaphat W (Dove Medical Press, 2022)
Saowapak Junhasavasdikul, Panyu Panburana, Sommart Bumrungphuet, Wirada Dulyaphat Department of Obstetrics and Gynecology, Division of Maternal Fetal Medicine, Faculty of Medicine, Mahidol University, Ramathibodi Hospital, Bangkok, ThailandCorrespondence: Wirada Dulyaphat, Division of Maternal-Fetal Medicine, Department of Obstetrics and Gynecology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, 10400, Thailand, Tel +66-873017028, Fax +66 02-2011416, Email wirada.dul@mahidol.ac.thObjective: Gestational diabetes mellitus (GDM) has an impact on fetal adrenal gland size and volume, which are greater in the GDM population. This study used 2D and 3D ultrasound scanning to determine the correlation of fetal adrenal gland size and volume with fructosamine levels, HbA1c levels, estimated fetal weight (EFW), and neonatal birth weight in GDM patients.Methods: This study included eighty singleton pregnant women diagnosed with GDM between 24- 28 weeks of gestation. During weeks 32- 34 of gestation, the length, width, and depth of the fetal zone and total adrenal gland were measured using transabdominal 2D ultrasound. Virtual organ computer-aided analysis (VOCAL) software was used to evaluate fetal zone and total adrenal gland volume in 3D ultrasound. All the participants were followed until delivery. Pearson's correlation analysis was conducted to examine the correlation between fetal adrenal gland ultrasound measurements and the factors of interest.Results: The study consisted of sixty-six (82.5%) pregnant women with diet-controlled GDM (GDMA1) and fourteen (17.5%) pregnant women with insulin-managed GDM (GDMA2). There was no difference in fetal adrenal gland measurements between the diet-controlled (GDMA1) and the insulin-managed (GDMA2) groups. All the participants had achieved optimal glucose levels at the time of ultrasound acquisition. The total adrenal gland length and fetal zone volume had statistically significant positive correlations with EFW (r = 0.69, p = 0.02 and r = 0.84, p = 0.01, respectively). After adjusting for EFW, only the fetal zone volume was significantly correlated with fructosamine levels (adjusted-OR = 2.4, 95% CI: 1.5, 3.9, p = 0.01) and HbA1c levels (adjusted-OR = 2.5, 95% CI: 1.6, 4.3, p = 0.01).Conclusion: The fetal zone volume is correlated with EFW, fructosamine levels, and HbA1c levels. This non-invasive technique may be beneficial as an indirect marker for glycemic monitoring in GDM.Keywords: fetal adrenal gland, three- dimensional ultrasound, two- dimensional ultrasound, fructosamine level, correlation, gestational diabetes mellitus